Notes on Purusia Lane, Juninia Lane, and Sibapipunga Martins & Galileo (Coleoptera, Cerambycidae, Lamiinae), and description of a new species of Juninia - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2022)
The differences between Purusia Lane, 1956, Juninia Lane, 1966, and Sibapipunga Martins & Galileo, 1993 are commented, especially the almost non-existence of morphological characters separating females from these three genera. A new provisional key to genera of Hemilophini with 12-segmented antennae is provided. Juninia raberi, a new species from Panama is described. Additionally, the type locality of Amphionycha annulifera Kirsch, 1889 is corrected, and the holotype is illustrated for the first time.